2015
DOI: 10.1177/1687814015618155
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ribs on flow parameters and laminar heat transfer of water–aluminum oxide nanofluid with different nanoparticle volume fractions in a three-dimensional rectangular microchannel

Abstract: This article aims to study the impact of ribs on flow parameters and laminar heat transfer of water-aluminum oxide nanofluid with different nanoparticle volume fractions in a three-dimensional rectangular microchannel. To this aim, compulsory convection heat transfer of water-aluminum oxide nanofluid in a rib-roughened microchannel has been numerically studied. The results of this simulation for rib-roughened three-dimensional microchannel have been evaluated in contrast to the smooth (unribbed) three-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(29 citation statements)
references
References 34 publications
(28 reference statements)
1
28
0
Order By: Relevance
“…The long life and dependability of these tools are influenced by several factors. The technology industries need components with compact devices 5,6 . Hwang et al 7 talk about the increasing use of micro‐turbines in industrial applications, which have a smaller efficiency in particular.…”
Section: Introductionmentioning
confidence: 99%
“…The long life and dependability of these tools are influenced by several factors. The technology industries need components with compact devices 5,6 . Hwang et al 7 talk about the increasing use of micro‐turbines in industrial applications, which have a smaller efficiency in particular.…”
Section: Introductionmentioning
confidence: 99%
“…According to empirically validated relationships, thermophysical properties of solid Aluminum-oxide nanoparticles [24] and Aluminum-oxide-Water nanofluid such as density, thermal capacity, thermal conductivity coefficient and dynamic viscosity for different volume fractions of the solid nanoparticles are listed in Table 2.…”
Section: Momentum Equationmentioning
confidence: 99%
“…Hang et al [8] numerically investigated the heat transfer performance of a microchannel heat sink with different nanofluids. Akbari et al [9] studied laminar flow and heat transfer parameters of water/Al 2 O 3 nanofluid with different nanoparticle volume fractions inside a rectangular microchannel and found that using rough surfaces in microchannel leads to higher heat transfer. Behnampour et al [10] numerically investigated laminar flow and heat transfer parameters of water/AgO nanofluid with different nanoparticle volume fractions in a rectangular microchannel and showed that by increasing fluid velocity, an optimized trade-off can be obtained between heat transfer, hydrodynamic behavior of nanofluid, and the performance evaluation criteria (PEC) variations.…”
Section: Introductionmentioning
confidence: 99%